Visuospatial, oculomotor, and executive reading skills evolve in elementary school, and errors are significant: a topological RAN study - Lecce, Mario; Miazza, Daniela; Muzio, Carlo; Parigi, Maria; Miazza, Alessandra; Bergomi, Mattia G. (Frontiers in Psychology, 2024)
This research investigates the development of visuospatial and oculomotor reading skills in a cohort of elementary school children. Employing a longitudinal methodology, the study applies the Topological serial digit Rapid Automated Naming (Top-RAN) battery, which evaluates visuospatial reading skills through metrics addressing crowding, distractors, and voluntary attention orientation. The participant pool comprises 142 students (66 males, 76 females), including 46 non-native speakers (21 males, 25 females), representing a diverse range of ethnic and racial backgrounds. The Top-RAN dataset encompasses performance, error, and self-correction metrics for each subtest and student, underscoring the significance of these factors in the process of reading acquisition. Analytical methods include standard dimensionality reduction, clustering, and classification algorithms, consolidated into a Python package to facilitate reproducible results. The findings indicate that visuospatial readingabilities vary according to the task and demonstrate a marked evolution over time, as seen in the progressive decrease in execution times, errors, and self-corrections. This pattern supports the hypothesis that the growth of oculomotor, attentional, and executive skills is primarily fostered by educational experiences and maturation. This investigation provides valuable insights into the dynamic nature of these skills during pivotal educational stages.